Implementasi Zakat dan Pajak Rumah Kos di Kelurahan Bukit Harapan Kecamatan Soreang Kota Parepare - Hannani (Institut Agama Islam Negeri Parepare, 2020)
Nowadays a boarding house business or business is very much in demand by the community because the benefits of a boarding house business are very promising, especially in areas close to tertiary institutions because locations close to tertiary institutions have better prospects. It's just that often the boarding house owner forgets about his obligation to pay zakat and tax from the rental of his boarding house. This study aims to determine how the implementation and barriers to the implementation of zakat and boarding house tax in Bukit Harapan Village, Soreang District, Parepare CityThis study uses a qualitative descriptive approach, and obtains data from primary and secondary data. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used is qualitative data.The results of this study indicate that the implementation of zakat and boarding house tax is that the boarding house owner has not fully issued the zakat and paid the boarding house tax because there are some obstacles that make the implementation not implemented properly.